Penyuluhan Cuci Tangan Pakai Sabun (CTPS) Pada Yayasan Pendidikan Al-Yasiriyah Bersaudara - Muhammad Bagas F; Lili Nurmaliza; Lubis, Nur Azizah; Sihombing, Juliana Sion; Andilala; Salim; Mohamad Aji Prasetia; Lubis, Muhammad Arif Fadhillah; Nursiah (Unity Academy, 2023)
Personal hygiene represents an important indicator that can influence a person's health. Each individual can start practicing personal hygiene by paying attention to their routine when carrying out regular handwashing activities. Regularly washing hands is a habit that should be developed in daily life. The hands are used in daily activities to interact with various types of objects or make physical contact, such as shaking hands or touching objects touched by other people. Some adults, as well as children and students, often ignore the simple activity of washing hands. This has the potential to increase the possibility of microorganisms such as bacteria and viruses developing on the hands. The outreach activity on hand washing with soap at the Al-Yasiriyah Bersaudara Foundation aims to distribute hand washing education in six (six) steps. The purpose of this activity is to inform parents, guardians, and students about the importance of regularly washing hands with soap to minimize the potential spread of disease-causing microorganisms. We carry out extension activities using lecture, discussion, question and answer, and demonstration methods. The results of the activity evaluation indicate that the average satisfaction index for the implementation of the activity is 86%. Additionally, each counseling participant provided an average assessment value of 3.46. This illustrates the usefulness of counseling activities in the hand hygiene habituation process among counseling participants.